La mise en tourisme du patrimoine paysager de la Vallée des peintres entre Berry et Limousin : un levier de développement rural ? - Edwige Garnier; Frédéric Serre (Projets de Paysage)
The Creuse Valley is a major component of the water landscapes of northern part of the Limousin region in France. From the 19th century onwards, the quality of the atmosphere and the light in this section of the valley near the region of the Berry attracted many artists, particularly impressionist artists. This profusion of artistic creativity focusing on the landscapes of the valley then fell into oblivion before the work of art historians exhumed this key period of local cultural history. The site was subsequently listed by the State in 1995. This regional heritage is now considered as an asset by local stakeholders who are developing a tourist centre at the crossroads of the Berry and Limousin regions. The purpose of the article is to examine both the process of heritage development in the Valley of the Painters and the economic and territorial benefits of development initiatives.